Answer:
a
Step-by-step explanation:
Radical roots occur as conjugate pairs
Given - 5 +
t is a root , then
- 5 -
t is also a root → a
By the law of cosines, the angle
![C](https://tex.z-dn.net/?f=C)
satisfies
![8.77^2=2^2+9^2-2\times2\times9\times\cos C](https://tex.z-dn.net/?f=8.77%5E2%3D2%5E2%2B9%5E2-2%5Ctimes2%5Ctimes9%5Ctimes%5Ccos%20C)
which reduces to
![\cos C=0.2246\implies C=\arccos(0.2246)\approx1.34422\text{ rad}](https://tex.z-dn.net/?f=%5Ccos%20C%3D0.2246%5Cimplies%20C%3D%5Carccos%280.2246%29%5Capprox1.34422%5Ctext%7B%20rad%7D)
which converts to approximately 77 degrees (this can be done my multiplying by 180 and dividing by pi).
Money of account is 58.19+2.74__60.85
The part that represents the solution to the inequality will be Part B shaded below first line and above second line.
<h3>How to depict the inequality?</h3>
From the information given, the equation of the first line will be:
y - 3 = (-3 - 3/2 + 4)(x + 4)
y - 3 = -1(x + 4)
y + x = -4 + 3
x + y = -1
The equation of the second line will be:
y + 3 = -1(x + 4)
y = x + 4 - 3
y = x + 1
This is plotted on the graph attached.
From the systems of equations, the statement that is correct about the two systems of equations is that They will have the same solution because the first equation of System B is obtained by adding the first equation of System A to 3 times the second equation of System A.
Learn more about inequalities on:
brainly.com/question/12215820
#SPJ1
Answer:
40:16, 16:40, 40/16, 16/40